Desain Dan Analisa Inverter Tiga Fasa Dengan Metode SVPWM Sebagai Penggerak Motor Induksi Tiga Fasa Pada Aplikasi Sepeda Listrik - Ronaldi Hutabalian; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Along with the increased use of fuel oil, so that necessary to manufacture in producing electric vehicles. One of them the electric bike. On an electric bike, motors drive consist of electric motors, power converters and electronic controllers are the mover of electric vehicle systems. This study discusses the three-phase inverter method Space Vector Pulse Width Modulation (SVPWM) as a three-phase induction motor drive in electric bike applications that are modeled by using Matlab / Simulink.The purpose of this study is to get the design of the three-phase inverter SVPWM as a three-phase induction motor drive 500 W, 50 V, 50 Hz and 750 rpm. The inverter design using battery voltage 48 V. Before the battery voltage is converted by an inverter, battery voltage must first be raised through a boost converter to 70,62 Volt. Through simulation with Matlab software is then obtained curve of sinusoidal voltage box, current, and speed of the motor in the unit pu SVPWM controlled by the system. In this study also tested against changes in the value of the fundamental frequency inverter. From the test results that the inverter can set the speed of the motor at a frequency of 20 Hz to 50 Hz. At the time of the frequency inverter 5-15 Hz current increases exceeding motor nominal current of 8.25 A.Keywords : Three Phase Inverter, Space Vector Pulse Width Modulation (SVPWM), Three Phase Induction Motor, Matlab/ Simulink, Electric bike.